(untitled) (Security Dialogues, 2023)
The smuggling of migrants is not a new phenomenon but in recent years it has attracted increasing international attention. In the last few years, migrant smuggling has become one of the most lucrative types of organized crime in the Balkans. This research article focuses on the issue of migrant smuggling as a contemporary transnational organized crime which is getting structurally stronger and more established. According to Frontex, the Western Balkans continues to be the most active migratory route into the European Union. From the beginning of the 2022 the number of irregular border crossings detected rose by 152% compared to 2021. The paper will present and analyse the official data of the judicial authorities. Also, a brief overview of the security implications of migrant smuggling to national security from 2015 until today will be given.